2017
DOI: 10.1016/j.memsci.2016.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of low-pressure nanofiltration: Membrane characterization, modeling, and understanding the multi-ionic interactions in water softening

Abstract: Recently, a novel class of low-pressure nanofiltration (NF) hollow fiber membranes, particularly suited for water softening and desalination pretreatment have been fabricated in-house using layer-by-layer (LbL) deposition with chemical crosslinking. These membranes can operate at exceedingly low pressures (2 bar), while maintaining relatively high rejections of multivalent ions. In spite of their great potential, our understanding as to what makes them superior has been limited, demanding further investigation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(90 citation statements)
references
References 56 publications
7
83
0
Order By: Relevance
“…Brine at 45 g/kg can easily be diluted down to 35 g/kg with the help of relatively inexpensive outfalls. Furthermore, if complete zero liquid discharge norms are in place, this stream could be re-circulated back to the RO inlet after softening and removing divalent ions using nanofiltration (NF)[69,70] or other means. Several configurations can be envisioned around the basic RO-ED configurations and operating parameters presented in this paper.…”
mentioning
confidence: 99%
“…Brine at 45 g/kg can easily be diluted down to 35 g/kg with the help of relatively inexpensive outfalls. Furthermore, if complete zero liquid discharge norms are in place, this stream could be re-circulated back to the RO inlet after softening and removing divalent ions using nanofiltration (NF)[69,70] or other means. Several configurations can be envisioned around the basic RO-ED configurations and operating parameters presented in this paper.…”
mentioning
confidence: 99%
“…[12] However,since NF membranes are not perfectly selective, some divalent ions can also pass through the membrane into the permeate.I no ne study,N Fw ith an applied pressure of 20 bar was only able to reject 50 %ofthe calcium ions (Ca 2+ ) and 71 %o ft he magnesium ions (Mg 2+ ). Alternatively,insearch of effective methods to eliminate divalent ions,r ecent work on cross-linked layer-by-layer polyelectrolyte nanofiltration hollow fiber membranes by Liu et al [16] and Labban et al [17] has demonstrated the selective rejection of multivalent ions at exceedingly low pressures, showing that advanced NF membranes may be useful for removing scalants from the feed stream without the precipitation step.A dditionally,c arbon nanotube composite and graphene oxide-incorporated polymeric membranes have been shown to exhibit greater mechanical stability and ability to purify water. In order to prevent scaling and provide afeed with the required purity level for BMED,asubsequent precipitation step may be applied after NF pretreatment.…”
Section: Nanofiltrationmentioning
confidence: 99%
“…[12] Theresulting NF permeate stream is then fed into the BMED system to produce NaOH and HCl with negligible scaling. Alternatively,insearch of effective methods to eliminate divalent ions,r ecent work on cross-linked layer-by-layer polyelectrolyte nanofiltration hollow fiber membranes by Liu et al [16] and Labban et al [17] has demonstrated the selective rejection of multivalent ions at exceedingly low pressures, showing that advanced NF membranes may be useful for removing scalants from the feed stream without the precipitation step.A dditionally,c arbon nanotube composite and graphene oxide-incorporated polymeric membranes have been shown to exhibit greater mechanical stability and ability to purify water. [18][19][20] In conjunction with different composite materials,o thers have improved the performance of nanofiltration by exploring different strategies to modify the surface of nanofiltration membranes, [18][19][20][21] which range from rapid co-deposition of polymers [21] to in situ surface reactions [18] to inkjet printing.…”
Section: Nanofiltrationmentioning
confidence: 99%
“…In this work, we present the development of a system-level model for NF hollow fiber modules, combining state-of-the-art NF modeling, based on the extended Nernst-Planck equation, with fundamental conservation laws that govern fluid flow and mass transfer in hollow fiber modules. The newly developed LbL1.5C membrane by Liu et al [4] is adopted in this study, while the model presented is validated against experimental results reported in a previous work [13]. To demonstrate the model's capabilities, a preliminary module design was proposed, and parametric studies were run to assess the viability of the LbL1.5C membrane for large-scale seawater desalination pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we develop a mathematical model to our knowledge the first to predict the performance of NF hollow fiber modules on the system-level, building from experiments run on a bench-scale setup. In an earlier study, we demonstrated the successful implementation of a membrane transport model, introduced by Geraldes and Alves [12] based on the extended Nernst-Planck equation, to the newly developed LbL hollow fiber membranes [13]. However, that model focused on coupon-sized systems, and did not take into consideration the streamwise variations that will be inherent in large-scale applications.…”
Section: Introductionmentioning
confidence: 99%